Effects of sulphur fertilization in organically cultivated faba bean - Omer, Zahra Saad; Nadeau, Elisabet; Stoltz, Eva; Edin, Eva; Wallenhammar, Ann-Charlotte (Agricultural and Food Science, 2020)
Optimal seed yield and quality requires that the sulphur (S) demand of faba bean (Vicia faba L.) is ensured. The effect of S fertilization on organic cultivated faba bean was investigated under field conditions during two growing seasons (2017–2018), in Sweden. Kieserite (MgSO4) and gypsum (CaSO4) were applied at a rate of 20 and 40 kg ha-1 to study the effect on faba bean growth, yield, crude protein (CP) content and amino acid (AA) composition. Gypsum and kieserite significantly increased S concentration of faba bean dry matter (DM) in 2017. The S concentration ranged from 0.20% to 0.23% of DM compared to 0.18% in the untreated control. In 2018, kieserite application at 40 kg ha-1 significantly increased S concentration to 0.15% compared to 0.12% in the untreated control. The faba bean plants did, however, not respond neither with increased growth nor increased seed yield. The seed quality in terms of CP and S-containing AA, was not affected by S fertilization, however, significant differences were observed between the experimental sites.